ความงามแห่งจิตวิญญาณในปัจฉิมบท “บางเรา บางใคร” กวีนิพนธ์ในรอบสามทศวรรษในฐานะครูของ “ไพฑูรย์ ธัญญา” "The spiritual valueon the poetry endingof “Bang-Row Bang-Khai”, the poetry in the 3rddecade of a teacher - poet, Phaitoon Tanya" - เมฆเมืองทอง ชมพูนุท (Chophayom Journal, 2017)
บทคัดย่อ บางเรา บางใคร เป็นกวีนิพนธ์ในรอบสามทศวรรษของ “ไพฑูรย์ ธัญญา” นักเขียนซีไรต์ ประจำปี 2530 และศิลปินแห่งชาติ สาขาวรรณศิลป์ ประจำปี 2559บางเราบางใคร เป็นบทกวีนิพนธ์ที่สะท้อนความงามแห่งจิตวิญญาณของบทกวีในฐานะครูของ “ไพฑูรย ์ ธัญญา” บทกวีนิพนธน์ ี้ไดสื้บทอดแนวคิดเรื่องวรรณศิลปแ์ ละความงามแห่งจิตวิญญาณ “ไพฑูรย์ ธัญญา” สะท้อนการวิพากษ์วิจารณ์ปัญหาสังคมพร้อมเสนอแนวทางแก้ไข และการปลูกฝังความดีงามแก่สังคมด้วยจิตสำนึกแห่งความเป็นครู ที่มีจุดเด่นในแบบการจบแบบไม่จบทำให้ผู้อ่านขบคิดถึงบทสรุปที่แตกต่างหลากหลาย ABSTRACT “Bang-RowBang-Khai” is the poetry in the 3 rddecade of “Phaitoon Tanya”, the 1987 S.E.A. “Write award winner and Thailand National Artist (Literature) 2016 from “Bang-Row Bang- Khai” is spiritual value by being a teacher-poet. This poetry was presented inthe continuity and creation of literary convention in his poetry which reflects the concept of literary techniques and spiritual value of poetry. Being a teacher-poet, Phaitoon Tanya, highlights current social issues in order to make people aware of the seriousness of the problems. The highlight of the poetry is the ending without conclusion in order for the readers to have various conclusions of their own.